Cadherin preserves cohesion across involuting tissues during C. elegans neurulation - Kristopher M Barnes; Li Fan; Mark W Moyle; Christopher A Brittin; Yichi Xu; Daniel A Colón-Ramos; Anthony Santella; Zhirong Bao (eLife, 2020)
The internalization of the central nervous system, termed neurulation in vertebrates, is a critical step in embryogenesis. Open questions remain regarding how force propels coordinated tissue movement during the process, and little is known as to how internalization happens in invertebrates. We show that in C. elegans morphogenesis, apical constriction in the retracting pharynx drives involution of the adjacent neuroectoderm. HMR-1/cadherin mediates this process via inter-tissue attachment, as well as cohesion within the neuroectoderm. Our results demonstrate that HMR-1 is capable of mediating embryo-wide reorganization driven by a centrally located force generator, and indicate a non-canonical use of cadherin on the basal side of an epithelium that may apply to vertebrate neurulation. Additionally, we highlight shared morphology and gene expression in tissues driving involution, which suggests that neuroectoderm involution in C. elegans is potentially homologous with vertebrate neurulation and thus may help elucidate the evolutionary origin of the brain.